Aliphatic Alcohol, Acid, Ester and Other Constituents from Rice Straw of Oryza sativa - Chung, Ill-Min; Yun, Jae-Yeon; Lee, Joohyun; Ahmad, Ateeque (Asian Journal of Chemistry, 2013)
Eight compounds, n-octacos-9-enyl propionate (1), 1-tetratriacontanol (2), b-sitosterol (3), n-tetracontan-15a-ol (4), tritriacontan-4,12-diene (5), n-tritetracontan-5a-ol (6), gallic acid (7) and b-sitosterol-3-O-b-D-glucoside (8) have been isolated and identified from methanol extract of rice straw of Oryza sativa. The structures of these known compounds were elucidated with the help different spectroscopic techniques.